Investigation on the damage to Kumamoto Castle stone wall related to the 2016 Kumamoto Earthquakes - T. Ohsumi (International Association of Lowland Technology, 2017)
A major earthquake with a magnitude (MJMA) 6.5 foreshock and a MJMA 7.3 main shock occurred at 1:25 on April 14 and 21:26 on April 16, 2016, respectively, in the Kumamoto region. According to the Kumamoto Castle research center, the reported damages to Kumamoto Castle included 23 important cultural properties, the 27 reconstructed structures and 523 stone wall deformations. Thirty percent of all of the stone walls were damaged. The stone wall foundation used two different construction techniques from the Kato age and Hosokawa age. The damage patterns with respect to the shapes of the stones in the walls were investigated and compared. The damaged stone walls which related to the main shock, were mainly constructed Hosokawa ages. In addition, the damage patterns in the reinforced concrete reconstructed Castle Keeps (Tensyu) / turrets (Yagura) and existing historical wooden structures were compared.